2016
DOI: 10.1186/s40064-016-3043-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trauma associated appraisals in trauma survivors from collectivistic cultures

Abstract: Appraisals are a key feature in understanding an individual’s experience; this is especially important when the experience is a traumatic one. However, research is diminutive when looking at the interaction between trauma appraisals and culture in relation to posttraumatic stress disorder using qualitative methodologies. This study explored cultural differences in perceptions and appraisals of trauma using three qualitative focus groups with community members (n = 11) from collectivistic cultures who had exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Culture influences how individuals interpret and react to adverse events, how they express their distress, their willingness to disclose information, the meaning they ascribe to experiences and symptoms, their help-seeking attitudes and behaviors, and their strengths, resources, and coping strategies (Drožđek & Wilson, 2007;SAMHSA, 2014). For example, research suggests that white, middle-class, Western conceptions of trauma focus primarily on individual adversity rather than the communal adversities typically emphasized in collectivist cultures (Engelbrecht & Jobson, 2016;Summerfield, Loughrey, Nikapota, & Parry-Jones, 1997). Existing screening tools rarely account for cultural differences, nor have most measures been tested and found to be valid and reliable across different cultural groups-current evidence on culturally competent screening for adversity is limited and findings are inconsistent (Chu & Lieberman, 2010;Elliot & Urquiza, 2006;Lieberman, Chu, Van Horn, & Harris, 2011).…”
Section: Cultural Backgroundmentioning
confidence: 99%
“…Culture influences how individuals interpret and react to adverse events, how they express their distress, their willingness to disclose information, the meaning they ascribe to experiences and symptoms, their help-seeking attitudes and behaviors, and their strengths, resources, and coping strategies (Drožđek & Wilson, 2007;SAMHSA, 2014). For example, research suggests that white, middle-class, Western conceptions of trauma focus primarily on individual adversity rather than the communal adversities typically emphasized in collectivist cultures (Engelbrecht & Jobson, 2016;Summerfield, Loughrey, Nikapota, & Parry-Jones, 1997). Existing screening tools rarely account for cultural differences, nor have most measures been tested and found to be valid and reliable across different cultural groups-current evidence on culturally competent screening for adversity is limited and findings are inconsistent (Chu & Lieberman, 2010;Elliot & Urquiza, 2006;Lieberman, Chu, Van Horn, & Harris, 2011).…”
Section: Cultural Backgroundmentioning
confidence: 99%
“…Hechanova, Waelde, & Ramos (2015) suggested that because social support is highly valued by Filipinos, group-based interventions were a good healing environment. Engelbrecht and Jobson (2016) suggested that group therapies are effective in collectivist cultures because they reduce isolation, shame, isolation, helplessness, and passivity.…”
Section: Psychological Research On Urban Societymentioning
confidence: 99%
“…The persistent need for surrogate decision makers to feel validated in their self-appraisal of ICU events by clinicians is consistent with the commonly accepted stress appraisal conditions in other psychology literature. 31 In our data, we frequently saw statements that seemed to reflect misunderstandings of clinical course or treatment decisions. The recollections of providers' expected roles and presumed intent reflected frustration with the care processes and workflow at academic medical centres.…”
Section: Discussionmentioning
confidence: 87%
“…Another strength of our study is our inclusion of participants several years after the ICU experience, which helps us gain a better sense for the persistence of the experience of critical illness even years after the ICU admission. 31 Distinguishing the impact of the critical illness and ICU admission from the psychological impact of the illness itself are both aspects that likely merit attention in the development of optimal approaches to support patients, families and clinicians in the ICU.…”
Section: Open Accessmentioning
confidence: 99%